Review of Ophthalmology - Friedman, N. J. Neil J. (Elsevier, 2018)
Designed to maximize easy retention and quick recall, Review of Ophthalmology, 3rd Edition, by Drs. Neil J. Friedman, Peter K. Kaiser, and William B. Trattler, is the best-selling review book you can trust to get you successfully through your exams. An efficient, easy-to-digest format distills key information into highly relevant bullet points. You'll quickly master what you need to know in all subspecialty areas, including the latest information on today's standard diagnostic techniques, medical treatments, and surgical options.